2019
DOI: 10.1088/1361-6463/ab28f9
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic regimes induced by nanosecond pulsed discharges in air: mechanism of vorticity generation

Abstract: The mechanisms controlling the hydrodynamic effects induced by nanosecond pulsed discharges applied between two pin electrodes in air at atmospheric conditions are investigated experimentally and numerically. A cylindrical plasma kernel is formed between the electrodes during the discharge. After the discharge, schlieren images show that the cylindrical kernel evolves in different ways depending on the gap distance: (1) for short gap distances (), the cylindrical kernel collapses to form a torus-like structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 49 publications
(60 reference statements)
3
32
0
Order By: Relevance
“…Depending on the applied voltage and PRF, two discharge regimes can be obtained, namely, NRP glow and the NRP spark discharges, as defined in [16,17]. The NRP glow discharges mainly have a chemical impact on the flame [18], while NRP spark discharges influence the flame hydrodynamically, thermally, and chemically [19][20][21]. First, it is interesting to note that for a given setting of the plasma actuation, both NRP glow discharges and NRP spark discharges may be observed, with a similar breakdown voltage of about 6 kV (peak voltage in figures 4a and 4b).…”
Section: Electrical Properties Of the Plasma Dischargesmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the applied voltage and PRF, two discharge regimes can be obtained, namely, NRP glow and the NRP spark discharges, as defined in [16,17]. The NRP glow discharges mainly have a chemical impact on the flame [18], while NRP spark discharges influence the flame hydrodynamically, thermally, and chemically [19][20][21]. First, it is interesting to note that for a given setting of the plasma actuation, both NRP glow discharges and NRP spark discharges may be observed, with a similar breakdown voltage of about 6 kV (peak voltage in figures 4a and 4b).…”
Section: Electrical Properties Of the Plasma Dischargesmentioning
confidence: 99%
“…During an NRP spark discharge, the energy is deposited in a very short time and P d can be calculated considering heating at constant volume of the gas in the discharge channel. For the conditions of this study, the fraction of total energy deposited by the discharges that goes into ultra-fast heating, E thermal , is assumed to be 20% of the total deposited energy, as for example in [19]. Only NRP spark discharges are considered in this model.…”
Section: Hydrodynamic Effect Of the Plasma Actuationmentioning
confidence: 99%
“…In some cases, we also employ a computational fluid dynamics (CFD) model to analyze the temperature evolution of the laser plasmas. The CFD simulations are performed using a Riemann solver developed in-house based on the Navier–Stokes equations 16 , 45 , 46 . Previous work by the authors has demonstrated that the initial (end-of-the pulse) state of the NIR breakdown kernel can be obtained iteratively by fitting the experimental 1-D scattering profiles at early times as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This energy is deposited during subsequent reflections at t = 90 ns and t = 180 ns. For detailed descriptions of the oscillograms, see [11,21].…”
Section: Measurement Equipmentmentioning
confidence: 99%
“…Non-equilibrium NRP (Nanosecond Repetitively Pulsed) spark discharges last a few nanoseconds, with an overvoltage of a few kilovolts. Applied at a repetition rate in the 10 to 100 kHz range in a combustible mixture, they produce thermal, chemical, and hydrodynamic effects [11][12][13] that promote the combustion process [2,4,6,14]. These benefits have been extensively demonstrated at low and atmospheric pressures, and some recent studies [15,16] have also shown positive effects for the ignition of lean mixtures at pressures up to 16 bar.…”
Section: Introductionmentioning
confidence: 99%